Odpowiedzi

  • Użytkownik Zadane
2010-03-09T18:17:51+01:00
2x-5(0,2-5)=3(x-5)-20
2x-1+25=3x-15-20
2x+24=3x-35
-x=-59
x=59

2x+3(22-x)=x-3(8-x)
2x+66-3x=x-24+x
-x+66=2x-24
-3x=-90
x=30

2(x-1)-3(1+3x)=3x-7(6+x)-5
2x-2-3-9x=3x-42-7x-5
-7x-5=-4x-47
-3x=-42
x=14


6-0,25x=0,75x-6
-x=-12
x=12

-2(x-10)-x=2(x-15)
-2x+20-x=2x-30
-3x+20=2x-30
-5x=-50
x=10

2(x+5)+4=2(x-3) +x
2x+10+4=2x-6+x
2x+14=3x-6
-x=-20
x=20


-15-5(2x-8)=59-4(3x-2)
-15-10x+40=59-12x+8
-10x+25=-12x+67
2x=42
x=21
2010-03-09T18:19:49+01:00
2x-5(0,2-5)=3(x-5)-20
2x-1+25=3x-15-20
2x-3x=-15-20+1-25
-x=-59
x=59


2x+3(22-x)=x-3(8-x)
2x+66-3x=x-24+3x
2x-3x-x-3x=-24-66
-5x=-90
x=18


2(x-1)-3(1+3x)=3x-7(6+x)-5
2x-2-3-9x=3x-42-7x-5
2x-9x-3x+7x=-42-5+2+3
-3x=-42
x=14


6-0,25x=0,75x-6
-0,25x-0,75x=-6-6
-x=-12
x=12


-2(x-10)-x=2(x-15)
-2x+20-x=2x-30
-2x-x-2x=-30-20
-5x=-50
x=10


2(x+5)+4=2(x-3) +x
2x+10+4=2x-6+x
2x-2x-x=-6-10-4
-x=-20
x=20


-15-5(2x-8)=59-4(3x-2)
-15-10x+40=59-12x+8
-10x+12x=59+8+15-40
2x=42
x=21